Zur Orthographie der englischen Entlehnungen im Dänischen - Szubert, Andrzej (Folia Scandinavica Posnaniensia, 2007)
The paper is an attempt to describe the spelling of English loan-words in the Danish language. It has been verified whether the spelling remains unchanged or whether it is assimilated. It has also been checked whether the assimilation follows a regular pattern.